EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA IPUN (IPAS IS FUN) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Hani Kurnia Rahmawati; Yeni Dwi Kurino; Yuyun Dwi Haryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low critical thinking ability of fourth grade students at SDN Banjaran and SDN Kagok, Banjaran District, Majalengka Regency. The purpose of this study is to determine the differences in critical thinking abilities between students who learn using the problem-based learning model assisted by IPUN media (IPAS Is Fun). This research is a type of quantitative research with a quasi-experimental method in a non-equivalent control group design. The determination of this sample uses purposive sampling, data collection techniques are carried out using test techniques in the form of essay questions, pretests and posttests of critical thinking abilities. Data analysis techniques used are normality tests, homogeneity tests, independent sample t-tests and n-gain. The results of the study show (1) There is a difference in critical thinking abilities of students who learn using the problem-based learning model assisted by IPUN media (IPAS Is Fun) which is higher than students who learn using the direct instruction model. (2) There is an increase in critical thinking abilities of students who receive learning using the problem-based learning model assisted by IPUN media (IPAS Is Fun) which is higher than students who receive learning using the direct instruction model. Thus, it can be concluded that the application of the problem-based learning model assisted by IPUN media (IPAS Is Fun) is effective in improving the critical thinking skills of fourth-grade students at SDN Banjaran, Banjaran District, Majalengka Regency.